Environmental Fiscal Policy for Sustainable and Efficient Renewable Energy (UNWE Yearbook, 2021)
The article is focused on the appropriate factors for the effective implementation of fiscal policy instruments that lead to more efficient and competitive models for the production of renewable energy. These models became an efficiency tool for value creation and delivery for the customers as part of the transition management for sustainable development. The analysis is based on in-depth case studies in Bulgaria and Belgium and compares the polycentric approaches for governance.